Development of the Korean Community Health Determinants Index (K-CHDI) - Go, Dun-Sol (PLoS One, 2020)
This study developed and validated a Korean community health determinants index (K-CHDI), which can be used to assess the health status of the community. To develop composite indicators, we followed the guidelines of the Joint Research Centre of the Organization for Economic Cooperation and Development. We reviewed previous studies and formed a theoretical framework to systematize our domains and indicators, which were decided through a Delphi survey of healthcare experts. Data on indicators were obtained from the Korean Statistics and Community Health Survey. We applied the Min-Max normalization method and measured weights by the analytic hierarchy process. Health outcomes were estimated using mortality, years of life lost, years lived with disability, and disability-adjusted life years by standardizing sex and age. The value of the index is between 0 and 1; higher values indicate more positive health determinants. K-CHDI for 250 subnational regions (cities, counties, and districts, or Si·Gun·Gu) were correlated with health outcomes. The correlation coefficient was stronger in large cities than in medium-sized areas and small areas, and the higher the K-CHDI group, the higher the coefficient. The K-CHDI represents a reference standard for estimating health status using health determinants as composite indicators at the subnational level.